2002
DOI: 10.1007/s00213-001-0975-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of buprenorphine sublingual tablet maintenance on opioid drug-seeking behavior by humans

Abstract: High-dose buprenorphine attenuated opioid drug-seeking behavior, heroin craving self-reports and increased sensitivity to alternative reinforcement. These beneficial effects were retained when high-dose buprenorphine was administered on alternate days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…The marketed preparations of buprenorphine alone (Comer et al, 2001;Greenwald et al, 2002) and buprenorphine formulated in combination with naloxone have been examined for their efficacy in reducing opioid self-administration using a PR procedure. Comer and colleagues (2001) demonstrated that buprenorphine maintenance was effective at reducing intravenous heroin self-administration, with larger doses (16 mg/day) demonstrating greater efficacy than smaller doses.…”
Section: Buprenorphine: Laboratory Evaluation Of a Partial Agonist Trmentioning
confidence: 99%
“…The marketed preparations of buprenorphine alone (Comer et al, 2001;Greenwald et al, 2002) and buprenorphine formulated in combination with naloxone have been examined for their efficacy in reducing opioid self-administration using a PR procedure. Comer and colleagues (2001) demonstrated that buprenorphine maintenance was effective at reducing intravenous heroin self-administration, with larger doses (16 mg/day) demonstrating greater efficacy than smaller doses.…”
Section: Buprenorphine: Laboratory Evaluation Of a Partial Agonist Trmentioning
confidence: 99%
“…Studies of the treatment effectiveness of maintenance doses of buprenorphine are few compared to those of methadone, and the results are mixed. However, on measures of retention rates and illicit opioid use, buprenorphine has been found to be as effective as, or better than, methadone when prescribed at higher doses (8-16 mg/day) (Foltin and Fischman, 1996;Johnson et al, 1992;Kosten et al, 1988;Ling et al, 1996;Schottenfeld et al, 1997;Strain et al, 1994aStrain et al, , b, 1996, whereas lower dose regimens (2-4 mg/ day) are less effective (Greenwald et al, 2002;Ling et al, 1998;Montoya et al, 2004). Furthermore, there are reports that buprenorphine maintenance reduces craving for cocaine (Foltin and Fischman, 1996) and, to varying degrees, reduces cocaine consumption as measured by urine analysis in human opioid addicts (Johnson et al, 1992;Kosten et al, 1988;Ling et al, 1996;Schottenfeld et al, 1997;Strain et al, 1994aStrain et al, , b, 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs with lower efficacy than methadone and LAAM might be alternative treatments with less abuse and dependence liability. For example, buprenorphine is a low efficacy agonist that attenuates some abuse-related effects of heroin and other opioids (Greenwald et al, 2002;Strain et al, 2002); however, it is not clear whether buprenorphine has less abuse and dependence liability than other MOR agonists (Woods and Gmerek, 1985;Eissenberg et al, 1996;Winger and Woods, 2001;Comer and Collins, 2002).…”
Section: Discussionmentioning
confidence: 99%